PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) MATERI RELASI DAN FUNGSI PADA SISWA KELAS VIII SMPN 3 MAUPONGGO - Petronela Heriyana Putri; Stefanus Notan Tupen; Gregorius Taga (Program Studi Pendidikan Matematika, 2020)
This study aims to produce cooperative learning tools type Numbered Head Together (NHT) for Relationship and Function Material in class VIII students of SMPN 3 Mauponggo Satap 2019/2020 and to find out learning outcomes through the application of cooperative learning type of NHT, Relation and Function for students of SMPN 3 Satap Mauponggo. This research used in this research is experimental research. This study is the change that occurs between the pre-test and post-test values. Concomitant variable (Accompaniment): Student's pre-test score that must be reduced by covariance analysis. A sample is a portion (subsets) of a population. The sample in this study was 24 students of class VIII SMPN 3 Mauponggo Satap. The data analysis technique was obtained from the implementation stage using covariance analysis. Based on the results of the covariance analysis, it shows that F count = 67.35 is greater than F table = 4.28 with dk counting = 1 and dk denominator = 23 giving a significant value, indicating that cooperative learning type Numbered Head Together (NHT) is considered to improve learning outcomes for related material and functions class VIII students of SMPN 3 Satap Mauponggo 2019/2020.